Assessment of cold resistance in Momordica charantia L. accessions according to pollen germination at low temperatures in vitro - Yu. V. Fotev (Труды по прикладной ботанике, генетике и селекции)
Background. Bitter melon (Momordica charantia L.) is a vegetable and medicinal crop new for Russia. Its high heat demand is the main factor limiting the possibilities of its cultivation in a temperate continental climate. Evaluation and selection of more cold-resistant accessions is required for breeding new cultivars and expanding production. Previously obtained data attest to a possibility of assessing cold hardiness in the mature male gametophyte phase in vitro.Materials and methods. Eight bitter melon accessions, including parent forms, F1  hybrids and cv. ‘Gosha’, were grown in the unheated film greenhouse of the Central Siberian Botanical Garden, Novosibirsk (54°49’ N, 83°06’ E) for evaluation and selection for cold resistance. The ratio of pollen germination in vitro on a 15% polyethylene glycol solution with a molecular weight of 6000 (PEG 6000) with the addition of boric acid (0.006%) at a temperature of 10°C for 24 h to the same indicator at 25°C / 3 h (in %) was used as a criterion of cold resistance.Results. The cultivar ‘Gosha’, the accession Okinawa green from Japan, and the F1 hybrid (Feng Guang × Okinawa green) had the highest cold resistance, with the values of 59.7; 53.8 and 48.2%, respectively. The inheritance of cold resistance in F1 , assessed by the pollen germination index, depending on the crossing combination, changed from intermediate in two hybrids [F1 Feng Guang × Gosha) and F1 Feng Guang × Okinawa green)] to overdominant (positive heterosis) in the hybrid F1 (Feng Guang × Okinawa white).